2009
DOI: 10.1186/1472-6882-9-34
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial properties of Malaysian tualang honey against wound and enteric microorganisms in comparison to manuka honey

Abstract: Background: Antibiotic resistance of bacteria is on the rise, thus the discovery of alternative therapeutic agents is urgently needed. Honey possesses therapeutic potential, including wound healing properties and antimicrobial activity. Although the antimicrobial activity of honey has been effectively established against an extensive spectrum of microorganisms, it differs depending on the type of honey. To date, no extensive studies of the antibacterial properties of tualang (Koompassia excelsa) honey on wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
188
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(210 citation statements)
references
References 25 publications
20
188
1
1
Order By: Relevance
“…Minimum inhibitory concentration (MIC) was used to determine the lowest concentration of honey-in-water solution (w/v) at which the percentage inhibition is almost 100% [21,22]. The MIC before and after heat-treatment of SH hydrogen peroxide, although involved in antibacterial action [27][28][29][30][31][32].…”
Section: Antibacterial Capacity Assays Minimum Inhibitory Concentratimentioning
confidence: 99%
“…Minimum inhibitory concentration (MIC) was used to determine the lowest concentration of honey-in-water solution (w/v) at which the percentage inhibition is almost 100% [21,22]. The MIC before and after heat-treatment of SH hydrogen peroxide, although involved in antibacterial action [27][28][29][30][31][32].…”
Section: Antibacterial Capacity Assays Minimum Inhibitory Concentratimentioning
confidence: 99%
“…The antibacterial activity of the different honey samples was carried out by agar dilution and spectrophotmetric assays (Patton et al, 2006;Tan et al, 2009). For the agar dilution assay, double strength Mueller Hinton Agar (MHA) medium was prepared and incorporated with the different honey samples at concentrations (v/v Honey + MAH) of 5%, 10%, 20%, 30%, 40%, 50% and 75%.…”
Section: Antibacterial Testing By Agar Dilution Methodsmentioning
confidence: 99%
“…27,28 In a recent review, it was demonstrated that honey could prevent cancerogenesis through alteration of cell cycle molecular processes 19 and some studies reviewed the effectiveness of honey for wound healing. 18,29,30 Although several studies demonstrated the soft tissue wound healing effect of honey, 18,23,29,30 its effect on bone defects has not been evaluated. Hence, the aim of the current study was to evaluate the effect of honey on healing of mandibular bone defects in a rat model.…”
Section: 5005/jp-journals-10024-2210mentioning
confidence: 99%
“…17 The antibacterial and anti-inflammatory effects of honey have been reported in several studies. [18][19][20][21][22][23] In addition, honey contains vitamin C concentration three times more than plasma, 24 which could accelerate tissue regeneration. 25 A recent clinical trial showed the effectiveness of honey as a dressing for dry socket.…”
Section: 5005/jp-journals-10024-2210mentioning
confidence: 99%